Comprehensive genetic testing improves the clinical diagnosis and medical management of pediatric patients with isolated hearing loss - Jiale Xiang; Yuan Jin; Nana Song; Sen Chen; Jiankun Shen; Wen Xie; Xiangzhong Sun; Zhiyu Peng; Yu Sun (BMC, 2022)
Abstract Purpose Genetic testing is widely used in diagnosing genetic hearing loss in patients. Other than providing genetic etiology, the benefits of genetic testing in pediatric patients with hearing loss are less investigated. Methods From 2018-2020, pediatric patients who initially presented isolated hearing loss were enrolled. Comprehensive genetic testing, including GJB2/SLC26A4 multiplex amplicon sequencing, STRC/OTOA copy number variation analysis, and exome sequencing, were hierarchically offered. Clinical follow-up and examinations were performed. Results A total of 80 pediatric patients who initially presented isolated hearing loss were considered as nonsyndromic hearing loss and enrolled in this study. The definitive diagnosis yield was 66% (53/80) and the likely diagnosis yield was 8% (6/80) through comprehensive genetic testing. With the aid of genetic testing and further clinical follow-up and examinations, the clinical diagnoses and medical management were altered in eleven patients (19%, 11/59); five were syndromic hearing loss; six were nonsyndromic hearing loss mimics. Conclusion Syndromic hearing loss and nonsyndromic hearing loss mimics are common in pediatric patients who initially present with isolated hearing loss. The comprehensive genetic testing provides not only a high diagnostic yield but also valuable information for clinicians to uncover subclinical or pre-symptomatic phenotypes, which allows early diagnosis of SHL, and leads to precise genetic counseling and changes the medical management.